A STUDY ON THE STUDENTS ABILITY IN PRONOUNCING DIPHTHONGS AT STKIP PGRI PASURUAN - Ninik Suryatiningsih (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2014)
Speaking is a complex skill, which has different components such as: pronunciation, vocabulary, grammar, and fluency. In accordance with the problems of the study, this researchis intended to know the students? ability in pronouncing diphthongs. The study was held inPronunciation and Dictation class of second semester students of STKIP PGRI Pasuruan. Thisresearch is a descriptive study, the researcher analyzed their ability in pronouncing Englishdiphthongs by classifying their score based on the classification of the score levels. Then theresearcher analyzed the errors made by them in pronouncing English diphthongs. As a result,the researcher found that many students have incorrect pronunciation in pronouncing Englishdiphthongs. Almost all of the students have difficulties in pronouncing diphthongs. The averagescore of the students is 73, laid between 60 74. The data showed that their ability inpronouncing English diphthongs was in fair category. The researcher found that the difficultdiphthong was pronounce by the students is diphthong /oU/. And for the easiest diphthong waspronounce by them is diphthong /aU/